The Phenomenon of Doom Spending Among Generation Z: A Review of Islamic Legal Sociology and Jasser Auda's Maqasid Syariah on Family Economic Resilience - Arifin, Syamsul; Jamilah; Burhanuddin Susamto (Muhammadiyah University of Surabaya, 2025)
Doom spending is an impulsive consumptive behavior that emerges as a form of escape from psychological pressure, stress, or economic uncertainty. Generation Z, as the most digitally exposed generation, is particularly susceptible to this behavior due to the strong influence of social media and digital lifestyles. This study aims to analyze the impact of doom spending on the economic resilience of Generation Z families and to examine this phenomenon through the perspective of Jasser Auda's Maqasid Syariah with an Islamic legal sociology approach. The research method used is an empirical-sociological approach with data collection techniques through observation, interviews, and documentation. The results of the study show that doom spending has a negative impact on the ability of families to meet basic needs, save money, and maintain financial stability. The main driving factors include fear of missing out (FOMO), digital social pressure, and low financial literacy. In Jasser Auda's sociological perspective of law, doom spending is not merely an individual moral behavior, but a social phenomenon that indicates a weak internalization of maqasid al-syariah values, particularly hifz al-māl (preserving wealth) and hifz al-'aql (preserving reason). Auda emphasizes that Islamic law is a dynamic system that connects divine values with social reality. Therefore, the solution to doom spending must be directed at social and spiritual reconstruction, by integrating the principles of maslahah (benefit), tawazun (balance), and mas'uliyyah (social responsibility) in the consumption behavior of Muslim families. This study affirms the importance of synergy between modern financial literacy and maqasid sharia values in building family economic resilience in the digital age, so that the consumption behavior of Generation Z can be directed towards sustainable and equitable prosperity. Keywords: Doom Spending, Generation Z, Family Economic Resilience, Maqasid Sharia, Islamic Legal Sociology.